ANALISIS KOMPENSASI FINANCIAL DAN NON FINANCIAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. TELKOMSEL PALEMBANG - Su’aidy (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
This study aims to determine how the effect of compensation on employee productivity at PT. Telkomsel Palembang. The research model used in this research is the method of observation, interviews, questionnaires, and literature studies which are carried out systematically based on the research objectives. The sample in this study were 32 employees of PT. Telkomsel Area Palembang using the field research method or field study, where researchers directly distribute questionnaires to respondents who are considered eligible and can provide sufficient information. The analysis technique used is validity, reliability, regression, and Ttest. The results of the study show that compensation has a positive and significant effect on employee productivity. This makes compensation a variable that affects employee productivity at PT. Telkomsel Area Palembang.